Assessing the Role of Cyberbiosecurity in Agriculture: A Case Study - Drape, Tiffany; Magerkorth, Noah; Sen, Anuradha; Simpson, Joseph; Seibel, Megan; Murch, Randall Steven; Duncan, Susan E. (Frontiers in Bioengineering and Biotechnology, 2021)
Agriculture has adopted the use of smart technology to help meet growing food demands. This increased automation and associated connectivity increases the risk of farms being targeted by cyber-attacks. Increasing frequency of cybersecurity breaches in many industries illustrates the need for securing our food supply chain. The uniqueness of biological data, the complexity of integration across the food and agricultural system, and the importance of this system to the U.S. bioeconomy and public welfare suggests an urgency as well as unique challenges that are not common across all industries. To identify and address the gaps in awareness and knowledge as well as encourage collaborations, Virginia Tech hosted a virtual workshop consisting of professionals from agriculture, cybersecurity, government, and academia. During the workshop, thought leaders and influencers discussed (1) common food and agricultural system challenges, scenarios, outcomes and risks to various sectors of the system; (2) cyberbiosecurity strategies for the system, gaps in workforce and training, and research and policy needs. Meeting sessions were transcribed and analyzed using deductive coding methodology. Major themes included resulting in challenges, solutions, viewpoints, common vocabulary. From the results of the analysis, it is evident that there is a lack of cyberbiosecurity training and resources available to all groups who participated. Participants were uncertain about future pathways for training, implementation, and outreach related to cyberbiosecurity. Recommendations include creating training and education, continued interdisciplinary collaboration, and recruiting government involvement to speed up better security practices related to cyberbiosecurity.